Preliminary Investigation on Electrochemical Parameters of Lake Waters in and around Miri City, Malaysia - Prasanna, Mohan Viswanathan; Ramasamy, Nagarajan; Aruchunan, Elayaraja; Chidambaram, S. (Universiti Putra Malaysia, Universiti Pertanian Malaysia Press, 2014)
Surface water samples were collected from 16 Lakes in and around Miri City to assess the electrochemical parameters includes pH, Electrical conductivity (EC), Total dissolved solid (TDS), redox potential (Eh), resistivity and salinity. Sampling locations for monitoring were selected in the vicinity of major roads, industries, settlements and agricultural region. Interpretation of data shows that the surface water in the central region of the study area is polluted by various anthropogenic activities, while in the southern part is within the limits of guideline values. This kind of investigation is essential in the study area to save the resources for future perspective. Further detailed studies are also needed to get a clear picture of the surface water quality in Miri city and for future sustainable management of this resource.